Do Website Quality, Fashion Consciousness, and Sales Promotion Increase Impulse Buying Behavior of E-Commerce Buyers? - Allysha Tiffany Wiranata; Arga Hananto (Indonesian Journal of Business and Entrepreneurship (IJBE), 2020)
The prevalence of online shopping also gave rise to irrational shopping behavior like impulse buying, which makes up a large share of e-retailer revenue. This study’s objective was to analyze the factors that affect impulse buying (i.e., website quality, sales promotion, and fashion consciousness) within the context of apparel/fashion product purchase. Besides, this study also sought to examine the role of sales promotion in moderating the relationship between website quality and impulse buying. An online survey with a final sample size of 211 respondents was carried out using Google Forms and analyzed with Confirmatory Factor Analysis and multiple regression analysis (using R Statistical Software) to analyze four hypotheses. The result indicated that website quality did not affect impulse buying, while sales promotion and fashion consciousness was found to affect impulse buying positively. However, the role of website quality was still critical, since it still played a role as a hygiene factor. Once website quality interacted with sales promotion, it could positively affect impulse buying. Keywords: fashion consciousness, impulse buying, sales promotion, website quality